2013
DOI: 10.1097/qad.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

HIV-exposed infants

Abstract: Summary Each year over a million infants are born to HIV infected mothers though with scale up of prevention of mother to child transmission (PMTCT) interventions, only 210,000 of the 1.3 million infants born to mothers with HIV/AIDS in 2012 became infected. Current programmatic efforts directed at infants born to HIV-infected mothers are primarily focused on decreasing their risk of infection, but this emphasis on maternal interventions has meant follow-up of exposed infants has been poor. Programs are strugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 50 publications
1
9
0
1
Order By: Relevance
“…Because the dates of maternal HIV infection and viral suppression were not known, we could not confirm the HIV-exposure status among HIV-uninfected control siblings, but we suspect that most if not all were exposed since they were born within ~5 years of their HIV-infected sibling. HIV exposure, even in the absence of infection, has been associated with multiple abnormalities that may affect the development and function of the kidney in childhood [ 29 31 ]. On the other hand, the high prevalence of renal dysfunction among controls could also reflect a high community prevalence of renal dysfunction among children, possibly related to the known high prevalence of schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Because the dates of maternal HIV infection and viral suppression were not known, we could not confirm the HIV-exposure status among HIV-uninfected control siblings, but we suspect that most if not all were exposed since they were born within ~5 years of their HIV-infected sibling. HIV exposure, even in the absence of infection, has been associated with multiple abnormalities that may affect the development and function of the kidney in childhood [ 29 31 ]. On the other hand, the high prevalence of renal dysfunction among controls could also reflect a high community prevalence of renal dysfunction among children, possibly related to the known high prevalence of schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…The current recommendation of HAART for all HIV-infected pregnant women (the B+ option) is promising and will serve to reduce infant HIV exposure in Sub-Saharan Africa [ 50 ]. However, there will be a lag time until infant HIV exposure is eliminated in the region, thus elucidation of the clinical relevance of infant’s exposure to maternal HIV [ 20 , 51 - 53 ] and its impact on altered T-cell populations should remain a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Progress in the prevention of mother-to-child transmission of HIV has led to a significant reduction of mother-to-child HIV transmission rate, increasing the population of HIV-exposed uninfected (HEU) infants ( 1 3 ). Indeed, HEU infants are a growing population with over a million infants born every year from HIV-infected mothers ( 2 ). Studies have shown that HEU infants are more vulnerable to diseases than infants born from HIV free mothers ( 4 8 ).…”
Section: Introductionmentioning
confidence: 99%